Aprendizagens e relações no tempo e espaço escolares: suas ressignificações no contexto do Programa de Ensino Integral do Estado de São Paulo (PEI) - Barbosa, Rafael Conde (2016)
In this research I wondered: what all school subjects (students, teachers, principals and other employees) think about the Full-time Education Program (PEI) they belong to; what personal learning and relationships are established at school and what new meanings are developed by these subjects in school space and time. I started conjecturing that relations potentiated by PEI could become or were becoming Knowledge that put teachers, students and principals as protagonists of their action and their life projects. The defended thesis was that if school material and immaterial conditions are followed by an effective construction of a pedagogical proposal by all subjects involved, the Full-time school can be converted into a space in which everyone can learn, not only the curriculum content, but also to relate and to reframe the school environment. I have done a qualitative research with Observations and Interviews in two public schools, one Elementary school (last years) and a High school. Were interviewed students, teachers, area and general coordinators, principals, vice-principals and one coordinator of São Paulo state Secretariat of Education. The subjects´ speeches were grouped according to similarities presented, highlighting those singular and self aspects manifested in their speech and behavior observed by me, resulting in the following categories: a) material and immaterial conditions for program implementation and b) learn and relearn how to interact at different levels and work in the school enviroment. I used as a theoretical reference the Teixeira (1959, 1962), Libâneo, Oliveira and Toschi (2012), Paro (1988a, 1988b, 2010, 2011), Cavaliere (2007), Imbernón (2010) and Dayrell (1996, 2012) studies, among other authors, who research/researched relations between regular schools and full-time schools. The Thesis initial hypothesis was confirmed after my analyzes: relations developed in the participating schools convert these spaces in exchange and relationships sites beyond curricular knowledge, and promote learning that make these subjects promoters of their actions and learning-processes and builders of their life projects. Teachers and the management team are committed and enthusiastic about the work done. PEI offers pedagogical support in continuing education times with the general and area Professors coordinators. This commitment is reinforced and taken by these professionals when they recognize the students´ behavior transformation who become more aware of their role as students and proactive regarding their training, welcoming and integrating new colleagues to the program